Clinical Approach to Infection in the Compromised Host - Rubin, Robert H.; Young, Lowell S. (Springer US, 1994)
'With admirable clarity the authors-all highly regarded experts in their respective fields-present the clinician with a supremely readable and practical text. The emphasis here is pragmatic, although there is sufficient pathogenesis and physiology to provide a fine balance.'-Journal of the American Medical Association, from a review of the second edition. This updated and profusely illustrated edition is 75% larger than its first incarnation. New coverage includes transplantation medicine, AIDS, patient management, and host-parasite interactions